Farmer Learning Groups - Vidallo, Rene R.; Bayot, Ruvicyn S.; Rosimo, Magnolia M.; Gonsalves, Julian Francis (2019)
The poster presents how organizing and facilitating farmer learning groups would encourage sharing of knowledge and learnings from implementation of action research.